Identification and Prioritization of Grain Discharging Operations Risks by Using ORESTE Method - Jafari, Hassan (Journal of Asian Business Strategy, 2013)
Exposing the acts of unloader, sucker and Grab in the grain terminal of Imam Khomeini port by manipulating ORESTE and Shannon’s Entropy Methods in the three phases will lead to identification and prioritization of the grain discharging processes risks from the ship. In the first phase, by the analysis of the events and occurred incidents information bank about the surveyed matters and also setting brainstorming sessions with the terminal’s experts, 22 risks were identified. In the second phase by using from the Shannon’s Entropy, the criteria (occurrence frequency, severity and detection) were weighted. Then based on the mentioned criteria the identified risks were scored in form of a scale from 1 to 10. Finally according to the obtained scores of each risk, the ORSTE decision matrix was conducted and subsequently in the third phase by using this method, all of the identified risks were prioritized.